Jesus left loose ends : collected essays - Loader, William R. G., 1944- (Scholars collection., 2021)
"This collection of Bill Loader's essays is a wondrous gift for both the academy and the church. The relationship between scholarship and faith weaves as a thread throughout. I highly commend this book and can imagine myself returning to it often.'Robyn Whitaker, Senior Lecturer in New Testament, Pilgrim Theological College, University of Divinity."--Publisher.